Innovation Diffusion of Digital Application in Supporting Waste Management in Sidoarjo Regency - Badrudin Kurniawan; Tjitjik Rahaju; Tauran; Martintje Maria Hukubun (Journal La Sociale, 2024)
Indonesia's waste management capabilities are still weak. The majority of waste is still handled by collecting-transporting-disposing and even many are still not handled. This has caused many landfills to experience over capacity, including those in Sidoarjo Regency. However, the process of Reduce, Reuse, Recycle (3R) waste is also being carried out by the people of Sidoarjo Regency. Waste banks apply these principles and contribute significantly to reducing waste entering the landfill. Therefore, there needs to be an effort to improve the performance of waste banks, for example through training on the use of digital waste bank applications. The process of innovation diffusion is important so that work processes become more efficient and data can be stored properly. However, there are many obstacles in diffusing these innovations. This study aims to examine the diffusion innovation of digital application in supporting waste management in Sidoarjo Regency. Authors adopt qualitative research methods. The result shows that the innovation diffusion process encountered quite a lot of obstacles both from the change agent and from the client, in this case the waste bank administrator. Therefore, the objectives of the innovation diffusion have not been achieved.